Mitochondria as a Target for Future Diabetes Treatments - Franziska Thimm; Marten Szibor (University Library System, University of Pittsburgh, 2015)
Diabetes mellitus is rapidly becoming the world's most dangerous serial killer. Type 1 diabetes (T1D) is a currently incurable autoimmune disease marked by progressive, and eventually exhaustive, destruction of the insulin-producing pancreatic beta cells. Type 2 diabetes (T2D) describes the combination of insulin resistance in peripheral tissue, insufficient insulin secretion from the pancreatic beta cells, and excessive glucagon secretion from the pancreatic alpha cells. T1D as well as severe cases of T2D are treated with insulin replacement, which can merely be considered as life support for the acute phases of the disease. Islet replacement of insulin-producing pancreatic beta cells represents a potential treatment method for both insulin-depleted diabetes (T1D) and insulin-resistant diabetes (T2D) and may shift diabetes management from life saving measures to a cure. One of the key challenges in islet transplants is the generation of reactive oxygen species (ROS) and the associated oxidative stress, which restricts graft longevity. A major leak of ROS takes place during oxidative phosphorylation at mitochondrial electron transport chain (ETC). Additionally, hyperglycemia-induced superoxide (O2•-) production has been linked to the development and progression of diabetic complications, both macrovascular and microvascular. Decreasing ROS in diabetic patients may prevent the incidence of long term diabetes complications. This review provides an overview of the role of mitochondria in diabetes, introducing them as a possible target for future treatment of diabetes.